Assessing positive adaptation during a global crisis: The development and validation of the family positive adaptation during COVID-19 scale - Shoychet, Gillian; Browne, Dillon T.; Wade, Mark; Prime, Heather (Frontiers in Psychology, 2022)
The COVID-19 pandemic has negatively impacted the psychosocial functioning of children and families. It is important to consider adversity in relation to processes of positive adaptation. To date, there are no empirically validated multi-item scales measuring COVID-related positive adaptation within families. The aim of the current study was to develop and validate a new measure: the Family Positive Adaptation during COVID-19 Scale (Family PACS). The sample included 372 female and 158 male caregivers (73% White-European/North American; median 2019 income = 50,000 to 74,999 USD) of children ages 5- to 18-years-old from the United Kingdom (76%), the United States (19%), Canada (4%), and Australia (1%), who completed measures in May 2020. Participants responded to a 14-item survey indexing a range of perceived coping and adaptation behaviors at the beginning of the pandemic. An exploratory factor analysis yielded an optimal one-factor solution comprised of seven items related to family cohesion, flexibility, routines, and meaning-making (loadings from 0.44 to 0.67). Multigroup confirmatory factor analysis demonstrated measurement invariance across female and male caregivers, demonstrating that the factor structure, loadings, and thresholds did not vary by caregiver sex. There was evidence for concurrent validity with significant bivariate correlations between the Family PACS scores and measures of caregiver positive coping, parenting practices, couple satisfaction, and family functioning (correlations from 0.10 to 0.23), but not negatively-valenced constructs. Findings inform our conceptualization of how families have adapted to adverse pandemic-related conditions. Further, we provide preliminary support for the Family PACS as a practical tool for evaluating positive family adaptation during this global crisis, with implications for future widespread crises.